2020
DOI: 10.1038/s42005-020-00432-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface anchoring controls orientation of a microswimmer in nematic liquid crystal

Abstract: Microscopic swimmers, both living and synthetic, often dwell in anisotropic viscoelastic environments. The most representative realization of such an environment is water-soluble liquid crystals. Here, we study how the local orientation order of liquid crystal affects the motion of a prototypical elliptical microswimmer. In the framework of well-validated Beris-Edwards model, we show that the microswimmer’s shape and its surface anchoring strength affect the swimming direction and can lead to reorientation tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…If W > W crit , the pusher prefers to swim perpendicular to n ∞ . Similar results were obtained in [31] for the stable swimming direction of a single microswimmer in classical LC described by the Beris-Edwards model without conformation tensor C. Compared to the swimmer dynamics in non-viscoelastic nematics, the new finding here is that viscoelasticity affects the convergence rate of the swimmer's orientation to its stable swimming direction if χ < 0. A puller with weak planar anchoring whose preferred swimming direction is perpendicular to n ∞ rotates to its preferred swimming direction faster (see Figure 2(b)).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…If W > W crit , the pusher prefers to swim perpendicular to n ∞ . Similar results were obtained in [31] for the stable swimming direction of a single microswimmer in classical LC described by the Beris-Edwards model without conformation tensor C. Compared to the swimmer dynamics in non-viscoelastic nematics, the new finding here is that viscoelasticity affects the convergence rate of the swimmer's orientation to its stable swimming direction if χ < 0. A puller with weak planar anchoring whose preferred swimming direction is perpendicular to n ∞ rotates to its preferred swimming direction faster (see Figure 2(b)).…”
Section: Resultssupporting
confidence: 82%
“…In general, for a swimmer in LC, there are two preferred orientations: (i) a swimming direction favored due to the type of swimmer; (ii) another swimming direction favored due to the elongated shape of the swimmer together with the anchoring type. In the case when these two favored directions are different, critical behavior is found [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lintuvuori et al [ 16 ] have studied the reorientation dynamics of a spherical squirmer in nematic LC and found that at steady state pushers (pullers) swim parallel (perpendicular) to the nematic director. The analytical calculation showed that the reorientation dynamics of a spherical squirmer is governed by a nematodynamic toque associate with the squirmer’s flow field and anisotropic viscosity of the suspending medium [ 16 18 ]. This unique behaviour of the microswimmers was utilized to transport cargo of cells/particles along prescribed pathways determined by the local nematic director field over long distances [ 14 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A closer look into the theoretical literature shows that dynamics of microswimmers in LCs have been investigated using either the lattice Boltzmann method [ 16 ] or finite element method [ 18 ]. These methods solve the nematodynamics but do not include thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%